EANEKARAGAMAN SERANGGA PENGUNJUNG BUNGA PADA TANAMAN KAKAO (Theobroma cacao L) - Flora Pasaru; Alam Anshary; Abd. Wahid; Hasriyanty Hasriyanty; Desi Wahyuni Arsih (Institute of Computer Science (IOCS), 2026)
This study aims to determine the abundance and diversity of insects that visit the flowers of the cocoa plant (Theobroma cacao L.) based on the observation time (morning, afternoon and evening). This study was carried out from April to June 2025 in a cocoa plantation owned by farmers (cocoa plant age ? 10 years) in North Tada Village, South Tinombo District, Parigi Moutong Regency, Central Sulawesi Province. This study shows that during the morning period, approximately between 06:30 and 09:30 WITA, the highest presence or preference of insect pollinators on cacao plants was observed, accounting for 51.74% or a total of 789 individuals (N = 789; S = 9). These findings indicate that flower-visiting insects on cacao, which are predominantly pollinators (approximately 93.04%), generally exhibit peak visitation during the morning, coinciding with anthesis, as well as in the late afternoon.